Changes in Treg numbers and activity in papillary thyroid carcinoma with and without Hashimoto's thyroiditis. Issue 4 (April 2020) - Zhao, Na; Liu, Xin; Wu, Chao; Liu, Yuanchao; Zhao, Xiangnan; He, Xianghui
Background: Hashimoto's thyroiditis (HT) is a common autoimmune disease, and an increasing number of papillary thyroid carcinoma (PTC) cases are being diagnosed in HT patients. The aim of this study was to investigate the proportion and function of different T cell subtypes in peripheral blood, especially CD4 + Foxp3 + regulatory T cells (Tregs), in PTC with and without HT. We also studied the effect of HT on PTC. Methods: Flow cytometry was used to detect the proportions of CD4 + T cells, CD8 + T cells, CD4 + Foxp3 + Tregs, and the level of interleukin-10 (IL-10) secreted by CD4 + T cells in the peripheral blood of PTC patients with and without HT. AimPlex bead-based immunoassays were used to determine serum cytokine levels. Results: No significant differences were observed in the proportion of CD4 + or CD8 + T cells in the two groups of PTC patients. The percentage of CD4 + FoxP3 + Tregs and their levels of IL-10 were significantly lower in PTC patients with HT than in those without HT. Conclusions: Our findings suggest that CD4 + Foxp3 + Tregs have vital regulatory functions in the initiation and progression of PTC by secreting the inhibitory cytokine IL-10.